Influence of multifocal intraocular lenses on standard automated perimetry test results - AYCHOUA, N; JUNOY MONTOLIO, F; JANSONIUS, NM (Acta ophthalmologica (Oxford, England), 2012)
Purpose To evaluate the influence of multifocal intraocular lenses (MFIOLs) on standard automated perimetry (SAP) and size V perimetry test results. Methods Sixteen eyes of 16 patients with a diffractive MFIOL (median age 64 years) and 45 phakic eyes of 45 healthy subjects (median age 49 years) were included in this cross‐sectional case‐control study. All eyes underwent (1) SAP with the Humphrey Field Analyzer using a 30‐2 grid and the Swedish Interactive Threshold Algorithm standard strategy and (2) a full threshold test with stimulus size V (instead of the default size III). Our Main Outcome Measures were the mean deviation (MD; for SAP) and mean sensitivity (MS; for both SAP and size V perimetry). Results The MD of the SAP test results was on average 2.18 dB lower in MFIOL patients than in controls (P<0.001). For all 16 cases and an age‐matched subgroup of 18 controls, this difference was 2.05 dB (P=0.001). The age‐adjusted difference in MS between cases and controls was ‐2.34 dB (P<0.001). For size V perimetry, this was ‐1.67 dB (P<0.001). For a subset of test locations within 10 degree eccentricity, the age‐adjusted difference in MS between cases and controls was ‐2.35 dB for size III (P<0.001) and ‐1.96 dB for size V perimetry (P<0.001). Conclusion Patients with a diffractive MFIOL have a clinically relevant reduction of the visual sensitivity as assessed with SAP and size V perimetry.